Peningkatan Kapasitas Kelompok Sadar Wisata dan Pengembangan Potensi Wisata Ekonomi Desa Maitara Tengah Kota Tidore Kepulauan - Musdar Muhammad; Fajri Hatim; Bahrun Talib (Jurnal Masyarakat Mengabdi Nusantara, 2025)
Development to become a tourist village requires cooperation and participation of the entire village community to advance the village. Local communities play an important role in the development of tourist villages because the resources and unique traditions, culture inherent in the community are the main driving elements of tourist village activities.tareget activities of tourism awareness groups, village government and the people of Maitara Tengah village. PKM methods; lectures, practices and participant mentoring. Output; journal, video making and online media publication. The results of PKM activities were carried out on Saturday, with 37 participants, Tourism is developed for the progress of the village, Maitra Tenga village has the potential for marine tourism to be developed, besides that, tourism will also develop the income of the Maitara Tengah village community.